Responsiveness of Public Service Provision at the Population and Civil Registration Service: JEL Classification: H11, H83, D73, H41, O38 - Riski Ramadani; Gita Susanti (Journal La Bisecoman, 2026)
This study aims to analyze the level of responsiveness of public service delivery at the Population and Civil Registration Office of Bone Regency. Responsiveness is an important indicator of public service quality, reflecting the ability of officials to respond to community needs, complaints, and aspirations. This study used a qualitative, descriptive approach. Data were obtained through participatory observation, in-depth interviews with officials and the public, and documentation studies. Data analysis was conducted in three stages: data reduction, data presentation, and conclusion drawing, with validity testing using triangulation of sources, techniques, and time. The results showed that the general level of responsiveness of public services at the Bone Regency Population and Civil Registration Office is considered good. The ability of officials to respond to the public has been effective, with open, direct communication between the public and office officials. The accuracy and precision of services are also considered good because they are guided by Standard Operating Procedures (SOPs) and an electronic-based service system. However, the speed of service still faces obstacles in terms of network aspects and limited number of officials. In addition, the ability to respond to public complaints is quite good, with online complaints via Google Forms. These findings emphasize the importance of improving human resource capacity and optimizing information technology to strengthen the responsiveness and quality of public services in the regions.